FORMULASI DAN UJI PERTUMBUHAN RAMBUT KELINCI DARI SEDIAAN HAIR TONIC KOMBINASI EKSTRAK DAUN SELEDRI (Apium graveolens Linn) DAN DAUN MANGKOKAN (Polyscias scutellaria (Burm.f.) Fosberg) - Siti Jubaidah; Ria Indriyani; Hayatus Sa'adah; Heri Wijaya (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Apium graveolens Linn and Polyscias scutellaria (Burm.f.) leaves are empirically widely used to stimulate hair growth. The purpose of this research is to combine celery leaf extract and mangkokan leaf extract formulated in hair tonic. The hair tonic preparations made were evaluated by performing a physical test of the preparation and knowing the best concentration of celery leaf extract and mangkokan leaf extract on rabbit hair growth. The hair tonic were prepared in 3 formulations with the ratio of Celery leaf extract and mangkokan leaf extract (5:5 ; 7,5:2,5 and 2.5:7,5)% w / v. The positive control used is hair tonic Minoxidil 2%. Physical tests of the preparation include organoleptic test, pH and viscosity test. Hair growth activity test is done by applying hair tonic on the 3 rabbits shaved hair and hair growth measurements until the 21st day. The data of hair growth measurements were tested statistically by ANOVA test method. Based on the research result, it can be concluded that hair tonic combination of celery leaf extract and mangkokan leaf extract with ratio (7.5: 2,5)%, has average hair length 2,459 cm and hair weight 0,199 g is the optimum concentration in stimulating hair growth activity with positive control has average hair length 2,493 cm and hair weight 0,285 g. Test statistically there was no significant difference between extract and positive control. Keywords : Apium graveolens Linn, Polyscias scutellaria (Burm.f.) Fosberg, hair tonic.